Addressing Differences in Learning Readiness and Styles - Showstack, Jonathan (Revista Hipótese, 2018)
There are many different ways to consider the Summerhill School and the philosophy of A. S. Neill's education. My intention is not to add more scholarly data to existing literature on Neill's ideas, but to offer some brief reflections and ideas based on my own experiences and observations.
Keywords: Summerhill.; Learning; Experience